Porphyrinic MOF Film for Multifaceted Electrochemical Sensing - Zhou, Zhenyu; Mukherjee, Soumya; Hou, Shujin; Li, Weijin; Elsner, Martin; Fischer, Roland A. (Angewandte Chemie International Edition, 2021)
Electrochemical sensors are indispensable in clinical diagnosis, biochemical detection and environmental monitoring, thanks to their ability to detect analytes in real‐time with direct electronic readout. However, electrochemical sensors are challenged by sensitivity—the need to detect low concentrations, and selectivity—to detect specific analytes in multicomponent systems. Herein, a porphyrinic metal‐organic framework (PP‐MOF), Mn‐PCN‐222 is deposited on a conductive indium tin oxide (ITO) surface. It affords Mn‐PCN‐222/ITO, a versatile voltammetric sensor able to detect redox‐active analytes such as inorganic ions, organic hazardous substances and pollutants, including nitroaromatics, phenolic and quinone‐hydroquinone toxins, heavy metal ions, biological species, as well as azo dyes. As a working electrode, the high surface area of Mn‐PCN‐222/ITO enables high currents, and therefore leverages highly sensitive analysis. The metalloporphyrin centre facilitates analyte‐specific redox catalysis to simultaneously detect more than one analyte in binary and ternary systems allowing for detection of a wide array of trace pollutants under real‐world conditions, most with high sensitivity. Integration of a porphyrinic metal–organic framework on a conductive indium tin oxide surface affords an electrochemical sensor, Mn‐PCN‐222/ITO. Thanks to detecting several inorganic ions, organic hazardous substances and pollutants, Mn‐PCN‐222/ITO demonstrates multifaceted sensing with low detection limits. Benchmark sensing performances are set not only across several single components, but also in the corresponding binary and ternary mixtures.